1998
DOI: 10.1097/00005053-199801000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Further Parameters of Insight and Neuropsychological Deficit in Schizophrenia and Other Chronic Mental Disease

Abstract: Evidence has begun to accumulate which suggests that lack of awareness of illness in schizophrenia is related to and possibly the result of a cognitive deficit involving prefrontal cerebral dysfunction. This study further explores this relationship along with other domains of self-awareness in chronic schizophrenics and other subjects with serious mental disorders. One hundred eight schizophrenics and 21 bipolar subjects from three separate sites in Britain, Germany, and Canada were administered the Wisconsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(68 citation statements)
references
References 21 publications
5
56
0
7
Order By: Relevance
“…To our knowledge, nineteen studies with available data have compared bipolar patients to schizophrenic patients on this test. Nine studies did not find any difference between the two groups, suggesting that cognitive inflexibility, linked to prefrontal cortical dysfunction, is not specific to SZ [38, 44, 46, 52, 65, 70, 82, 84, 85]. The small effect sizes (range: 0.10–0.44) confirm that the differences between the diagnostic groups are subtle.…”
Section: Resultsmentioning
confidence: 95%
“…To our knowledge, nineteen studies with available data have compared bipolar patients to schizophrenic patients on this test. Nine studies did not find any difference between the two groups, suggesting that cognitive inflexibility, linked to prefrontal cortical dysfunction, is not specific to SZ [38, 44, 46, 52, 65, 70, 82, 84, 85]. The small effect sizes (range: 0.10–0.44) confirm that the differences between the diagnostic groups are subtle.…”
Section: Resultsmentioning
confidence: 95%
“…34,35 Cognitive impairments associated with SMI may negatively affect individuals_ ability to make decisions in their own best interest or appropriately weigh the risks versus benefits of specific sexual behaviors. 36 The prevalence of homelessness among SMI persons may be as high as 45%, 37 while the prevalence of HIV infection among SMI homeless persons has been found to be as high as 19%. 38 Sexual relationships in these circumstances are often transient, casual, and may be offered in exchange for shelter and/or food.…”
mentioning
confidence: 99%
“…2 More recently, other theories have emerged, but there remains scientific support for the denial theory -studies have shown a correlation between increased selfdeception and decreased insight in schizophrenia. 14,15 Moreover, multiple studies have established a positive correlation between insight and depression, supporting the theory that insight may be a psychological reaction to mental illness.…”
Section: Discussionmentioning
confidence: 75%